CO2-full factorial optimization of an ultra-high performance concrete mix design. Issue 4 (3rd April 2018) - Mosaberpanah, Mohammad Ali; Eren, Ozgur
Abstract : This article presents a factorial modelling, as well as an optimization, of the mix proportion of ultra-high performance concrete (UHPC) in terms of maximising the 28-day strength and minimising CO2 emissions. A full factorial design and desirability function optimization method were performed to find the best UHPC ingredient proportions. To improve the concrete properties, the concrete performance in terms of CO2 emissions and environment effects should be considered. Ultra-high performance with superior properties requires a large amount of cement, steel fibre and an admixture; however, from an environmental perspective, cement and admixtures and steel fibre are the important matter for global warming as cement production corresponds to 5% of all the CO2 emissions around the world. In addition, the 28-day compressive strength is one of the most important properties of concrete and is related to other mechanical properties; therefore, the 28-day compressive strength and carbon oxide emissions were selected as the responses to produce the green UHPC with high performance. The mix design parameters were the cement content ( C ), the steel fibre amount ( F ), the superplasticiser (SP), the silica fume amount (SF) and the water to cementitious ratio ( W / C ). The variables were compared by fine aggregate mass. The optimized ingredient mix designs are valid for the mixes with .18–.32 W / C ratio, .04–.08 steel fibre, .7–1.3 cement, .15–.30 silica fume, and .04–.08 superplasticiser by fine aggregate mass.